Karakteristik Semburan Bahan Bakar Aviation Gasoline dengan Nozzle Pesawat Cessna 172S - Ilminnafik, Nasrul; Dimas Endrawan, Putra; M Fahrur Rozy, Hentihu; Muh. Nurkoyim, Kustanto; Danang, Yudistiro (Indonesian Journal Publisher, 2024)
Avgas fuel is fuel from aviation engines, namely piston engine type aircraft, where the spray of this fuel is very influential on the life of a piston type aircraft engine. The characteristics of avgas fuel bursts, namely the distance, temperature and shape of the spray, are rarely studied in Indonesia, so with using experimental and varied data collection techniques, we obtained the characteristic results of the avgas type fuel spray and its mixture, where the mixture of 20% ethanol with a distance of 21 cm at a pressure of 3 bar is the lowest point of the fuel mixture spray temperature, namely reaching 15oC, the effect of The mixture of fuel with ethanol means spots on the walls and combustion chamber due to the mixture of alcohol containing water so that traces and water spots can become crust on the combustion chamber.